Konstytucja europejska wobec deficytu demokratycznego - Mrozowska, Sylwia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The problem of democratic deficit in European institutions did not draw the particular attention of either EU officials or the national leaders of member states over the long period of the European Community’s’ existence. The political discussion over the issue of EU democratization was revived by a speech delivered by German minister of foreign affairs, Joschka Fisher, at the Humboldt University on May 12, 2000. Presenting his vision of the future of European integration this German politician emphasized that it was necessary to solve the ‘problem of democracy’ among others. Shortly before this, democratic deficit had become the subject of a comprehensive scientific analysis. The literature of the subject examined sources, formulated the definitions of democratic deficit, and searched for the answers to the question ofwhat the European Union is, what democracy is and whether it is appropriate to talk about a democratic non-state.